2022
DOI: 10.1017/s0007114522003282
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and predictors of the Omega-3 Index in the UK Biobank

Abstract: Information on the Omega-3 Index (O3I) in the United Kingdom (UK) are scarce. The UK-Biobank (UKBB) contains data on total plasma omega-3 polyunsaturated fatty acids (n3-PUFA%) and DHA% measured by NMR. The aim of our study was to create an equation to estimate the O3I (eO3I) from these data. We first performed an interlaboratory experiment with 250 random blood samples in which the O3I was measured in erythrocytes by gas chromatography, and total n3% and DHA% were measured in plasma by NMR. The best predictor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
(99 reference statements)
2
8
0
Order By: Relevance
“…In this study examining the UK Biobank cohort, we confirm previously reported inverse associations of long chain omega-3 fatty acid concentrations with RDW [22] (Figure 2) and NLR [23] (Figure 3). The average estimated O3I of 5.59% in the UK Biobank cohort [27] is similar to that (~5.0%) reported in healthy individuals globally [28,29]. The average RDW in the UK Biobank cohort (13.5%) is similar to values (12.6-12.9%) reported in adults living in the US [30], including those free of cardiovascular disease (NHANES 1994(NHANES -2004 [31] and without clinical evidence of anemia or inflammation [22].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this study examining the UK Biobank cohort, we confirm previously reported inverse associations of long chain omega-3 fatty acid concentrations with RDW [22] (Figure 2) and NLR [23] (Figure 3). The average estimated O3I of 5.59% in the UK Biobank cohort [27] is similar to that (~5.0%) reported in healthy individuals globally [28,29]. The average RDW in the UK Biobank cohort (13.5%) is similar to values (12.6-12.9%) reported in adults living in the US [30], including those free of cardiovascular disease (NHANES 1994(NHANES -2004 [31] and without clinical evidence of anemia or inflammation [22].…”
Section: Discussionsupporting
confidence: 74%
“…Thirty-one percent of participants reported using fish oil supplements, and fatty fish were consumed by 56% of the cohort, factors contributing to a mean Omega3% of 4.42% (Table 3) and O3I = 5.59% [27]. In this cohort of 109,191 individuals, the correlation between Omega3% and DHA% was r=0.88.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“… 3 Based on Schuchardt et al. ( 20 ) . 4 An index of 0 means “average deprivation” in the United Kingdom; a negative value means less deprived than average, and a positive means more deprived than average.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the O3I values associated with these DHA levels, we used an equation described by Schuchardt et al. [ 20 ], which found a correlation between the observed O3I and estimated O3I (eO3I) of 0.83.…”
Section: Methodsmentioning
confidence: 99%